1984
DOI: 10.1037/0096-3445.113.3.329
|View full text |Cite
|
Sign up to set email alerts
|

Dreams and reality monitoring.

Abstract: Experiment 1 tested the counterintuitive prediction that memories for one's own dreams should not be particularly easy to discriminate from memories for someone else's dreams. Pairs of people reported dreams to each other that they had either dreamed, read, or made up the night before. On a test requiring subjects to discriminate events they had reported from those reported by their partner, subjects had more difficulty with real dreams than with dreams they read or made up. Experiment 2 provided evidence that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
70
0
10

Year Published

1988
1988
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(85 citation statements)
references
References 12 publications
4
70
0
10
Order By: Relevance
“…Rather, these reports are the result also of subjective metacognitive judgments, crucial for deciding whether a mental event is indeed a memory for experiences from one's past (Jacoby, Kelley, & Dywan, 1989;Johnson, Hashtroudi, & Lindsay, 1993;Koriat & Goldsmith, 1996;Mazzoni & Kirsch, 2002;Nelson & Narens, 1990). For example, judgments are at the core of the Source Monitoring Framework-which has shown that the subjective characteristics of mental experiences influence metacognitive decision-making (Johnson et al, 1993;Johnson, Foley, Suengas, & Raye, 1988;Johnson, Kahan, & Raye, 1984)-and also of the remember/know distinction used in much memory research (e.g., Lövdén, Rönnlund, & Nilsson, 2002;Tulving, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…Rather, these reports are the result also of subjective metacognitive judgments, crucial for deciding whether a mental event is indeed a memory for experiences from one's past (Jacoby, Kelley, & Dywan, 1989;Johnson, Hashtroudi, & Lindsay, 1993;Koriat & Goldsmith, 1996;Mazzoni & Kirsch, 2002;Nelson & Narens, 1990). For example, judgments are at the core of the Source Monitoring Framework-which has shown that the subjective characteristics of mental experiences influence metacognitive decision-making (Johnson et al, 1993;Johnson, Foley, Suengas, & Raye, 1988;Johnson, Kahan, & Raye, 1984)-and also of the remember/know distinction used in much memory research (e.g., Lövdén, Rönnlund, & Nilsson, 2002;Tulving, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…Based on their proposals, numerous research studies have been conducted to explore the characteristics that differentiate statements of varying origin, such as memories of actual events, imagination, dreams, fantasies, lies, or false memories derived from post-event information (Diges, 1995;Henkel, Franklin, & Johnson, 2000;Johnson, 1988;Johnson, Kahan, & Raye, 1984;Johnson, Foley, Suengas, & Raye, 1988;Lindsay & Johnson, 1989;Manzanero, 2006Manzanero, , 2009Manzanero & Diges, 1995;Manzanero, El-Astal, & Aróz-tegui, 2009;Schooler, Gerhard, & Loftus, 1986;.…”
Section: Introductionmentioning
confidence: 99%
“…If the image is elicited with considerable reflection, effort, or elaboration, then the internally generated memory should be easier to distinguish from that for an external event than if the image is elicited naturally or spontaneously. Johnson, Kahan, and Raye (1984) found, for example, that people experience more confusion in reality monitoring for their actual dreams than for dreams they simply make up. Presumably, memories for real dreams contain less information about the cognitive operations used in the generation process, making them harder to distinguish from memories for perceived events.…”
mentioning
confidence: 99%